Transformasi Menuju Keberlanjutan: Analisis QoS dan Maintenance Jaringan Pada Diskominfo Bengkayang yang Mendukung SDGs - Maya Sari; Andrew Joewono (Institut Shanti Bhuana, 2025)
Improving network quality and the effectiveness of digital infrastructure maintenance play an important role in supporting the achievement of the Sustainable Development Goals (SDGs). Through Quality of Service (QoS) analysis and network maintenance strategies at Diskominfo Bengkayang, this study shows that network quality generally meets ITU-T G.114 and Cisco standards, with a throughput of 6721 kb/s, packet loss of 0.200%, latency of 17.250699 ms, and jitter of 17.261801 ms. However, packet loss still exceeds the ideal limit (2%), which can affect the stability of digital services. The maintenance strategy implemented includes preventive and corrective maintenance, with an average recovery time of 1-3 hours. The main obstacles include limited technical human resources, lack of a real-time monitoring system, and the use of old network devices. This network quality improvement contributes to the achievement of SDG 9 (reliable infrastructure supporting the digitization of government services), SDG 11 (development of smart cities in Bengkayang), and SDG 17 (partnership with ISPs, academics, and the private sector). This research recommends the use of more comprehensive QoS parameters and infrastructure improvements to support better digital services in the future.